A fast transient RBAOT controlled DC-DC buck converter with dual-loop DC offset cancellation technique and constant switching frequency. (October 2021) - Liu, Lianxi; Sun, Mengna; Huang, Wenbin; Xu, Chengzhi
Abstract: A fast transient ripple-based adaptive on-time (RBAOT) controlled DC-DC buck converter is presented in this paper. Firstly, for improving the output DC accuracy while keeping the fast transient response, a dual-loop DC offset cancellation technique is proposed. The fast loop ensures fast transient response, and the slow loop to compensate for the output DC offset introduced by ripple injection. Secondly, considering the parasitic resistances of the devices, the proposed switching frequency compensation technique reduces the frequency variation in steady state regardless of the input output voltage and load current condition. The proposed buck converter has been fabricated using 0.18-μm CMOS process. Measurement results show that the proposed converter has an outstanding output DC accuracy, the output offset is less than 2 mV. Moreover, the switching frequency is centered at 2 MHz with less than 1.5% variation for an output of 1.8 V and inputs ranging from 2.1 to 3.6 V. The maximum conversion efficiency is up to 94.6%, and the transient response times are 2 and 3 μs at rising and falling edges, respectively.